POTENSI GUGATAN PRA PERADILAN SEBAGAI UPAYA MENGHALANGI PROSES PENYIDIKAN TINDAK PIDANA KORUPSI - Eko Hari Purwanto (Legal Spirit, 2020)
The purpose of this study is to find out what is meant by Pretrial and the scope of Pretrial in Indonesia. As well as how in practice the Pre-trial could be considered a matter that could hinder the investigation of the suspects, especially in corruption cases that are being handled by the Corruption Eradication Commission. Pretrial is the right of suspects and related parties granted by the Criminal Procedure Code especially Article 1 point 10 of the Criminal Code. Meanwhile, in relation to efforts that could hinder the investigation of corruption cases that are being handled by the Corruption Eradication Commission especially because the Corruption Eradication Commission cannot conduct a further investigation process prior to the decision of the Pre-trial submitted by the suspect